A Comparative Analysis of Waqf Sign Systems in the Indonesian Standard Braille Mushaf and the Madinah Braille Mushaf: An Application and Capability Approach Study at the Hikmah Mata Hati Foundation - Abdul Rosyid; Inayah Mardhatillah (SALAM: Jurnal Sosial dan Budaya Syar-i, 2025)
This study aims to conduct a comparative analysis of the waqf sign systems in the Indonesian Standard Braille Mushaf (MSB) and the Madinah Braille Mushaf (MBM), to examine their application in Braille Qur'an learning, and to evaluate their effectiveness through the lens of the capability approach. Employing a qualitative method with a comparative case study design, data were collected through observation, in-depth interviews, documentation studies, and limited trials at the Hikmah Mata Hati Foundation. The findings reveal that both mushafs share a fundamental functional similarity as tactile guides for waqf and ibtidā’ based on tajwid principles. However, significant differences exist in the quantity of signs, the Braille symbols employed, the presence of positional marker codes, and their underlying institutional standards. Users demonstrated adequate capability in recognizing and applying the waqf signs, which directly contributed to reading accuracy, fluency, comfort, comprehension of verse structure, and increased independence in reading the Braille Qur'an. Nevertheless, the dot marker code (3-6) system in the MSB was identified as potentially causing ambiguity, particularly with the lā waqfa fīh sign. It is concluded that both waqf sign systems are effective in facilitating reading capability, with their effectiveness highly dependent on the interplay between symbol design, learning processes, and user experience. Keywords: Waqf Signs, Standard Braille Mushaf, Madinah Braille Mushaf, Braille Qur'an, Capability Approach